2016
DOI: 10.3389/fpsyg.2016.01294
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Paralysis in Brazilian Folklore and Other Cultures: A Brief Review

Abstract: Sleep paralysis (SP) is a dissociative state that occurs mainly during awakening. SP is characterized by altered motor, perceptual, emotional and cognitive functions, such as inability to perform voluntary movements, visual hallucinations, feelings of chest pressure, delusions about a frightening presence and, in some cases, fear of impending death. Most people experience SP rarely, but typically when sleeping in supine position; however, SP is considered a disease (parasomnia) when recurrent and/or associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
0
9
0
2
Order By: Relevance
“…Importantly, supernatural agent imagery is a common feature of extreme forms of terrifying nightmares manifested in sleep paralysis, incubus dreams, horrifying lucid dreams, and psychiatric disorders such as nocturnal panic attacks, all of which frequently arise during REM sleep (e.g., Nordin, 2011; McNamara et al, 2018). Even though these parasomnias may, like narcolepsy, be considered as sleep disorders in their own right, they are characteristically observed in a variety of psychiatric disorders, such as major depressive disorder, anxiety, post-traumatic stress disorder, attention-deficit/hyperactivity disorder, schizophrenia, bipolar disorder, borderline personality disorder, and other psychopathological conditions such as substance abuse (e.g., Kirov and Brand, 2014; de Sá and Mota-Rolim, 2016; Molendijk et al, 2017; McNamara et al, 2018; Tempesta et al, 2018; Baird et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, supernatural agent imagery is a common feature of extreme forms of terrifying nightmares manifested in sleep paralysis, incubus dreams, horrifying lucid dreams, and psychiatric disorders such as nocturnal panic attacks, all of which frequently arise during REM sleep (e.g., Nordin, 2011; McNamara et al, 2018). Even though these parasomnias may, like narcolepsy, be considered as sleep disorders in their own right, they are characteristically observed in a variety of psychiatric disorders, such as major depressive disorder, anxiety, post-traumatic stress disorder, attention-deficit/hyperactivity disorder, schizophrenia, bipolar disorder, borderline personality disorder, and other psychopathological conditions such as substance abuse (e.g., Kirov and Brand, 2014; de Sá and Mota-Rolim, 2016; Molendijk et al, 2017; McNamara et al, 2018; Tempesta et al, 2018; Baird et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Modern research has confirmed that OBE can occur during the awake state ( Ehrsson, 2007 ), sleep ( Blackmore, 1982 ), or dreaming ( Irwin, 1988 ; LaBerge et al, 1988 ; de Sá and Mota-Rolim, 2016 ). According to Levitan et al (1999) , OBE can also happen during some LD, and both may share some features, such as sleep paralysis, vibrations and a sensation of floating out of body.…”
Section: Spiritismmentioning
confidence: 99%
“…: Лазарева 2018]). Существуют исследования парасомний в медицинской антропологии и психологии ( [Ness 1978;Cheyne et al 1999;Hinton et al 2005b;Adler 2011;Sharpless, Doghramji 2015;Cox 2015;de Sá, Mota-Rolim 2016;Ashford 2017] и др. ), однако в этих работах иной ракурс, для которого могут быть нерелевантны структура текста, взаимосвязи сюжета, мотивов и персонажей с другими фрагментами устной традиции, модели и механизмы мифологизации персонального опыта по лекалам народной культуры.…”
Section: парасомнии и текстовые моделиunclassified
“…Как это делают авторы ряда работ, не только медицинских и психологических, но и гуманитарных, например: «Сонный паралич представляет собой достаточно убедительное доказательство того, как определенный нейробиологический феномен может быть интерпретирован и очерчен в различных культурных контекстах. Полевые исследования, проведенные в различных частях мира, выявили за мириадами этнических и религиозных точек зрения один и тот же феномен» [de Sá,Mota-Rolim 2016: 1294, ср. также[Kompanje 2008;Cox 2015;Лазарева 2018].…”
unclassified